2021
DOI: 10.1590/1806-9282.20200784
|View full text |Cite
|
Sign up to set email alerts
|

Relations of heart-type and brain-type fatty acid-binding proteins with postoperative cognitive dysfunction in elderly patients undergoing spinal surgery

Abstract: OBJECTIVE:The aim of this study is to analyze the relations of heart-type fatty acid-binding protein (H-FABP) and brain-type fatty acidbinding protein (B-FABP) with postoperative cognitive dysfunction (POCD) in elderly patients undergoing spinal surgery.METHODS: One hundred and twenty-five patients who underwent spinal surgery were enrolled in this study. According to whether patients had POCD within 5 days after surgery, the participants were divided into POCD group and non-POCD group. Before surgery and 6 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Fatty acid-binding proteins (FABPs) are associated with lipid and energy metabolism, inflammatory mechanisms, and cognitive dysfunctions ( Furuhashi and Hotamisligil, 2008 ; Storch and Corsico, 2008 ; Teunissen et al, 2011 ; Jiang et al, 2021 ). Fabp7 is a kind of FABP expressed in mammalian astrocytes and neural progenitors.…”
Section: Role Of Astrocyte In Normal Sleep and Sleep Deprivationmentioning
confidence: 99%
“…Fatty acid-binding proteins (FABPs) are associated with lipid and energy metabolism, inflammatory mechanisms, and cognitive dysfunctions ( Furuhashi and Hotamisligil, 2008 ; Storch and Corsico, 2008 ; Teunissen et al, 2011 ; Jiang et al, 2021 ). Fabp7 is a kind of FABP expressed in mammalian astrocytes and neural progenitors.…”
Section: Role Of Astrocyte In Normal Sleep and Sleep Deprivationmentioning
confidence: 99%
“…Research has shown that it is elevated in the serum of patients with Alzheimer's and Parkinson's disease [22,50]. Moreover, FABP-7 has been proven to be increased in elderly patients with postoperative cognitive dysfunction who underwent spinal surgery compared to patients with no such dysfunction and before the procedure [52]. FABP-7 has been also investigated in relation to psychiatric diseases and it appeared that three single-nucleotide polymorphisms (SNPs) from FABP-7 showed nominal association with bipolar disorder [53].…”
Section: Fabp-7mentioning
confidence: 99%